Investigation Injection of Computational Thinking Skills with Scratch on Teachers Performance: A Mixed-Method Study - Marom, Saiful; Stevanus Budi Waluya; Scolastika Mariani; Bambang Eko Susilo; Wardono (Hipotenusa: Journal of Mathematical Society, 2024)
Currently, the injection of computational thinking skills in education is very important because these skills are needed in dealing with technological developments. Every teacher needs to be provided with this ability with the hope that later they will be able to inject it into every student at school. This article presents empirical experiences related to the injection of computational thinking skills for madrasah (Islamic Schools) teachers in Indonesia using the Scratch program for 60 teachers. The research method used is a mix method, namely a quantitative approach (experiment) and a qualitative approach. In quantitative analysis, two classes are used, namely experimental and control classes. In the initial stage, the measurement of computational thinking ability was carried out using 15 questions. The results of this study showed an increase in computational thinking skills in the experimental class, which was also accompanied by impressions given by participants who saw positive developments and significant explorative and practical uses in learning practices.